2008
DOI: 10.1089/tmj.2007.0086
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Management of Strabismus Using Telemedicine

Abstract: This study was undertaken to measure the effect of telemedicine consultation for diagnosis and treatment planning in cases of strabismus. Telemedicine consultation records of all patients on ORBIS Telemedicine Cyber-Sight that resulted in a final diagnosis of superior oblique palsy (SOP), Duane syndrome (DS), and Brown syndrome (BS) were collected. The following were then determined: (1) the clinical characteristics of patients in each category, (2) the diagnosis submitted by the doctor requesting consultation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 4 publications
0
18
0
Order By: Relevance
“…More often, the queries were from physicians of resource-limited origins and were responded to by a network of international experts. All of such cases were asynchronous and web-based teleconsultations ( 48 - 51 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More often, the queries were from physicians of resource-limited origins and were responded to by a network of international experts. All of such cases were asynchronous and web-based teleconsultations ( 48 - 51 ).…”
Section: Resultsmentioning
confidence: 99%
“…Of them, two were in the teledermatology areas that used a semi-structured form ( 60 ) and an online structured pre-consultation questionnaire (mostly to educate medical trainees) ( 61 ). In another case, a web-based structured format to upload patient-related information was established to determine the effect of teleconsultation in cases of strabismus ( 48 ). In two other cases, a structured interview was performed in acute stroke care by telephone consultation ( 62 ) and a standardized query form (including all relevant clinical information) were designed for teledermatology consultation ( 52 ).…”
Section: Resultsmentioning
confidence: 99%
“…There was high diagnostic concordance between mentor and the remote ophthalmologist; however, there was only treatment plan agreement 50% of the time. 86 Non-diabetic retinal disease. Our review showed that teleophthalmic MOCs have also been used for patients with non-diabetic retinal disease.…”
Section: Disease-specific Mocsmentioning
confidence: 99%
“…ORBIS International is a non-profit humanitarian organisation, which works with local communities and institutions to build eye health infrastructure and deliver sustainable, high-quality eye care. 4 The capacity building activities include short term teaching programmes, a flying eye hospital and web-based consultations. The web consulting system (Cyber-Sight) connects partner physicians with mentor physicians.…”
Section: Introductionmentioning
confidence: 99%